How do saxophonists communicate through bodily behavior? A contribution to embodied performance pedagogies - Moura, Nádia (2023)
Bodily movement is at the heart of high-quality performance and deserves proper attention in instrumental education curricula. This study presents an analysis of the bodily behavior of professional and university-level saxophone players (N = 20) conducted with the aim of developing pedagogical cues on embodied communication and expression during music performance. Participants performed five excerpts of the classical saxophone standard repertoire while motion capture, audio, and video data were recorded. A systematic observational procedure was carried out to analyze the relationship between movement and music, including gesture codification and score annotation of each of the 100 performance recordings, and further comparison between participants was made. Five gestural trends were extracted, related to expressive communication, pitch contour influence, rhythm and pulse influence, technique facilitation strategies, and full-body behaviors. Findings suggest saxophone players use gestures and postures as a resource for expressing significant musical locations, aiding perception of musical elements, and facilitating technical challenges. These insights contribute to the development of an embodied approach to instrumental teaching and learning, promoting body awareness, communicative and facilitative skills through movement education.